Friday

December 19, 2014

December 19, 2014

Posted by **vilma** on Friday, October 26, 2012 at 6:15pm.

your answer.

(a) x 2 fxg

(b) fxg fxg

(c) fxg 2 fxg

(d) fxg 2 ffxgg

(e) ; fxg

(f) ; 2 fxg

2. 4 pts. Consider the experiment of rolling two distinguishable fair dice. Let A be the

event where the two numbers appearing are relatively prime to each other. List the

elements of A.

3. 2 pts. A hand of ve cards is drawn from a standard deck of 52 cards. Let B be the

event that the hand contains ve aces. List the elements of B.

4. 8 pts. Let U = fa; b; c; d; e; f; gg;W = fa; b; dg;X = fb; d; eg, and Y = fa; e; f; g; g.

Find the following:

(a) W [ Y

(b) (X \W) [ Y

(c) Y \ (W [ X)

(d) (W \ Y )n(Y [ X)

5. 14 pts. Express each of the following events in terms of the events A;B; and C as

well as the operations of complementation, union and intersection. In each case, draw

the corresponding Venn-Euler diagram.

(a) at least one of the events A;B;C occurs;

(b) at most one of the events A;B;C occurs;

1

(c) none of the events A;B;C occurs;

(d) all three events A;B;C occur;

(e) exactly one of the events A;B;C occurs;

(f) events A and B occur, but not C;

(g) either A occurs or, if not, then B also does not occur.

6. 5 pts. Denote the complement of any set X as Xc. Show that for any two sets A

and B, (A [ B)c = Ac \ Bc.

7. 5 pts. Prove that n3 + 5 is divisible by 4 for all n 2 Z+.

**Answer this Question**

**Related Questions**

math - if f(x)= 5x+7 and g(x)=x^2-2 write the functions a. (fxg)(x) b. f(g(x))

Math - If f(x)=x^2-2 and g(x)=1/(3x) (x does not equal 0), find (fxg)(-2)

Math - If f(x)=x^2-2 and g(x)=1/(3x) (x does not equal 0), find (f+g)(x) and f(...

algebra - find (FxG)(X) and (GxF)(X) when f(x)=5x^2-1 and g(x)=2/x

college - find (FxG)(X) and (GxF)(X) when f(x)=5x^2-1 and g(x)=2/x

trig function - Suppose f(x)=cos x - sin x and g(x)=cos x + sin x. Explain why ...

trig function - Suppose f(x)=cos x - sin x and g(x)=cos x + sin x. Explain why ...

trig function - Suppose f(x)=cos x - sin x and g(x)=cos x + sin x. Explain why ...

trig function - Suppose f(x)=cos x - sin x and g(x)=cos x + sin x. Explain why ...

trig and combine function - Suppose f(x)=cos x - sin x and g(x)=cos x + sin x. ...